Effectiveness of managerial control tools in Local Authorities: The Case of Chipinge RDC - Mucheri, Praise (Midlands State University, 2020)
The main purpose of the study was to view the effectiveness of managerial control tools in Local Authorities at Chipinge Rural District Council. The main problem was that Chipinge Rural District Council still lags behind in terms of providing its services to the residents due to its poor financial base. The managerial controls is a global concern that stresses continuous improvements to fit the changing environment. Managerial control tools came to light due to the poor work performance and the centralized approaches that were used in delivering services. A review of the related literature was also carried out in a bid to establish what other authors say about the managerial control tools and service delivery in local authorities. The main sources of literature were acts of parliament, textbooks, the constitution and journals. The research design used was a case study research where one single unit is extensively studied in depth within a limited time scale. Interviews and questionnaires were used to collect data during the research. Data was presented in forms of tables, graphs and pie charts to illustrate research findings and responses gathered. It was found out that managerial control tools had a negative impact on work performance and results though they are also some positive effects, some improvements were needed in the control tools of Chipinge and some residents did not know whether control tools was being practiced or not in Chipinge. Conclusion and recommendations were made on how to improve the work performance and serve delivery process so that developmental goals, organizational vision and mission are easily achieved and services are accessible to everyone.